Direct sulfonylation of pyrazolones with sodium sulfinates catalyzed by TBAI in water. Issue 15 (11th April 2018) - Li, Li-Xia; Dong, Dao-Qing; Hao, Shuang-Hong; Wang, Zu-Li
Graphical abstract: Highlights: Reactions can be carried out using water as solvent. Different reaction mechanism from previous reports. An equivalent amount of iodine reagents was not needed. Abstract: An efficient sulfonylation reaction of pyrazolones with sodium sulfinates catalyzed by TBAI was established. A wide variety of valuable sulfonated pyrazolones were obtained in good to excellent yields using water as solvent.